Can Digital Orientation Assist Digital Marketing and E-Payments Perform Better for MSME Performance in Indonesia? - Oki Sudrajat; Lela Nurlaela Wati; Abdul Mukti Soma (Research Synergy Foundation, 2024)
Rapid development in the perfume industry has been accompanied by accelerated digitalization, which was unexpected by most Micro, Small and Medium Enterprises (MSMEs). Many MSMEs in this sector experience problems with access and knowledge of digital technology, especially in digital marketing and e-payment. Most MSME players are still learning and are slow to adopt digitalization in their perfume business. This research aims to analyze the influence of digital marketing, e-payment and digital orientation on the performance of perfume MSMEs in West Java Province. A sample of 100 respondents, company owners or managers, was selected using stratified sampling. Data analysis uses Structural Equation Modeling (SEM) and Moderated Regression Analysis (MRA). The results show that digital marketing and digital orientation have a positive and significant effect on MSME performance, while e-payment does not have a significant effect. Digital orientation also negatively and insignificantly moderates the influence of digital marketing and e-payment on MSME performance. Perfume MSMEs are advised to consider the role of digital orientation and optimize digital marketing strategies to improve their business performance.